BETWEEN LANGUAGES AND CULTURES: THE ROLE OF CONTINUOUS TRAINING IN TEACHER PROFESSIONAL DEVELOPMENT IN PORTUGAL - Monteiro, Sara Andreia Ali; Reis, Andreia Vieira (Revista Ibero-Americana de Humanidades, Ciências e Educação, 2025)
The aim of this study is to map out the trends in continuing teacher training courses in Portugal, accredited by the Scientific-Pedagogical Council for Continuing Training (CCPFC), particularly orientated towards issues related to linguistic and cultural diversity. The analysis methodology adopted consisted of a documentary review of the titles of the training courses available on the CCPFC website, seeking to identify aspects such as the topics covered, the target audience and the training methods proposed. The results indicate that although there are significant efforts to promote diversity training, there are still areas that need to be strengthened. Firstly, there is an urgent need to increase the supply of training courses that address specific challenges, particularly about inclusion strategies for pupils who do not speak Portuguese. In addition, there is a need to promote a better balance in the distribution of training between the different centers, encouraging partnerships between educational institutions and other relevant bodies. Another critical point concerns the adaptation of programs, which should be adjusted to the specificities of each school and subject area. In conclusion, it is argued that the diversification of content, target audiences and training modalities is crucial to creating more inclusive educational environments in line with the needs of an increasingly linguistically and culturally diverse education system.